(untitled) (مجلة إحالات, 2026)
The purpose of this search is , to explore the causes and backgrounds which is behind the downsizing of linguistic traditions, and the Western semantic of the role of writing, it considers it just a secondary residual, and an external physical technique to represent speech. In exchange for the absolute presence that the voice achieves, through the vitality of the pronouncement and its precedence, the visual, dimensional, writing embodied on a tangible surface eligible for this, just trying to regain that presence, with imperfect, distorted, and dangerous restoration, and dangerous according to these metaphysical backgrounds centered on logos, sound, and the philosophy of presence. And this is an ancient epistemological and linguistic tradition that continues today, as it will be an epistemic reference for the establishment of the sciences of language and linguistics, since Aristotle who saw that the sound is closer to the meaning, passing by Plato, which warned against writing, accusing it of encouraging laziness, arrival to De Saussure, who made sound a basis for the theory of sign and meaning.